1996
DOI: 10.1007/bf01718170
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phylogenetic analyses of hantaviral sequences amplified from archival tissues of deer mice (Peromyscus maniculatus nubiterrae) captured in the eastern United States

Abstract: Summary. The S and M segments of a hantavirus, enzymatically amplified from tissues of Cloudland deer mice (Peromyscus maniculatus nubiterrae) captured during 1985 in West Virginia, diverged from strains of Four Corners virus from the southwestern United States bymore than 16% and 6% at the nucleotide and amino acid levels, respectively. Phylogenetic analysis suggested that this virus strain (designated Monongahela) forms a possible evolutionary link between the Four Corners and New York hantaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…Abbreviations used: ELMC, El Moro Canyon; RIOS, Rio Segundo; RIOM, Rio Mamore; LN, Laguna Negra; AND, Andes; CAS, Castelo dos Sonhos; ARA, Araraquara; CDG, Cañ o Delgadito; SN, Sin Nombre; MGL, Monongahela; NY, New York; BAY, Bayou; BCC, Black Creek Canal; US, United States; CR, Costa Rica; BOL, Bolivia; PGY, Paraguay; ARG, Argentina; BRZ, Brazil; VEN, Venezuela; Rmeg, Reithrodontomys megalotis; Rmex, Reithrodontomys mexicanus; Omic, Oligoryzomys microtis; Clau, Calomys laucha; Olong, Oligoryzomys longicaudatus; ?, unknown; Sals, Sigmodon alstoni; Pman, Peromyscus maniculatus; Pmannub, Peromyscus maniculatus nubiterrae; Pleu, Peromyscus leucopus; Opal, Oryzomys palustris; Shis, Sigmodon hispidus. The partial S segment nucleotide analysis included HTN 76-118 [Schmaljohn et al, 1986]; DOB [Avsic-Zupanc et al, 1995]; SEO SR-11 [Arikawa et al, 1990]; El Moro Canyon RM-97 [Hjelle et al, 1994]; Rio Segundo [Hjelle et al, 1995a]; Rio Mamore (RIOM) OM-556 [Bharabwaj et al, 1997]; LN [Johnson et al, 1997]; AND [López et al, 1997]; Cañ o Delgadito [Fulhorst et al, 1997]; SN NM H10 [Spiropoulou et al, 1994], CC107, and CC74 ; Monongahela-1 [Song et al, 1996]; NY RI-1 [Hjelle et al, 1995c]; BAY [Morzunov et al, 1995]; BCC [Ravkov et al, 1995]; Tula Malacky/Ma370/94 , Moravia/5293Ma/94 and 76Ma/87 [Plyusnin et al, 1995a]; Isla Vista PC-SB-77 ; Prospect Hill [Parrington and Kang, 1990]; prairie vole hantavirus MO46 (GenBank accession U19303); PUU Vindeln/L20Cg/83 [Horling et al, 1995], Vranica [Reip et al, 1995], CG1820 [Stohwasser et al, 1990], Udmurtia/894Cg/91 and Evo/12Cg/93 [Plyusnin et al, 1995b], Sotkamo [Vapalahti et al, 1992], Virrat/25Cg/95 [Plyusnin et al, 1997], and 90-13 [Bowen et al, 1995]; Khabarovsk [Horling et al, 1996]. Belem, Brazil, in 1982[LeDuc et al, 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations used: ELMC, El Moro Canyon; RIOS, Rio Segundo; RIOM, Rio Mamore; LN, Laguna Negra; AND, Andes; CAS, Castelo dos Sonhos; ARA, Araraquara; CDG, Cañ o Delgadito; SN, Sin Nombre; MGL, Monongahela; NY, New York; BAY, Bayou; BCC, Black Creek Canal; US, United States; CR, Costa Rica; BOL, Bolivia; PGY, Paraguay; ARG, Argentina; BRZ, Brazil; VEN, Venezuela; Rmeg, Reithrodontomys megalotis; Rmex, Reithrodontomys mexicanus; Omic, Oligoryzomys microtis; Clau, Calomys laucha; Olong, Oligoryzomys longicaudatus; ?, unknown; Sals, Sigmodon alstoni; Pman, Peromyscus maniculatus; Pmannub, Peromyscus maniculatus nubiterrae; Pleu, Peromyscus leucopus; Opal, Oryzomys palustris; Shis, Sigmodon hispidus. The partial S segment nucleotide analysis included HTN 76-118 [Schmaljohn et al, 1986]; DOB [Avsic-Zupanc et al, 1995]; SEO SR-11 [Arikawa et al, 1990]; El Moro Canyon RM-97 [Hjelle et al, 1994]; Rio Segundo [Hjelle et al, 1995a]; Rio Mamore (RIOM) OM-556 [Bharabwaj et al, 1997]; LN [Johnson et al, 1997]; AND [López et al, 1997]; Cañ o Delgadito [Fulhorst et al, 1997]; SN NM H10 [Spiropoulou et al, 1994], CC107, and CC74 ; Monongahela-1 [Song et al, 1996]; NY RI-1 [Hjelle et al, 1995c]; BAY [Morzunov et al, 1995]; BCC [Ravkov et al, 1995]; Tula Malacky/Ma370/94 , Moravia/5293Ma/94 and 76Ma/87 [Plyusnin et al, 1995a]; Isla Vista PC-SB-77 ; Prospect Hill [Parrington and Kang, 1990]; prairie vole hantavirus MO46 (GenBank accession U19303); PUU Vindeln/L20Cg/83 [Horling et al, 1995], Vranica [Reip et al, 1995], CG1820 [Stohwasser et al, 1990], Udmurtia/894Cg/91 and Evo/12Cg/93 [Plyusnin et al, 1995b], Sotkamo [Vapalahti et al, 1992], Virrat/25Cg/95 [Plyusnin et al, 1997], and 90-13 [Bowen et al, 1995]; Khabarovsk [Horling et al, 1996]. Belem, Brazil, in 1982[LeDuc et al, 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there will also be other hantaviruses in circulation that are not yet discovered and hantaviruses are constantly coevoluting with their hosts. Also, new hosts are discovered that are also capable to carry hantaviruses: such as happened with insectivores (Okumura et al 2007;Song et al 2007). As a consequence, more research is needed on the presence and distribution of hantaviruses in the world and their potential impact on human health.…”
Section: Other Hantaviruses Not Yet Linked With Human Diseasementioning
confidence: 98%
“…If untreated, mortality rates are up to 5% (Southern Jr. and Sanford 1969). A survey in Senegal (Godeluck et al 1994) demonstrated that the African grassrat (Arvicanthis niloticus) and Mastomys huberti (Hubert's Mastomys) function as hosts for the pathogen.…”
Section: Tick-borne Relapsing Fevermentioning
confidence: 98%
See 1 more Smart Citation
“…In North America HPS in humans is also induced by e.g. Bayou virus Khan et al 1995;Hjelle et al 1996;Ksiazek et al 1997;Torrez-Martinez et al 1998), Black Creek Canal virus Ravkov et al 1995;Khan et al 1996), New York virus (Hjelle et al 1995;Morzunov et al 1998) and Monongahela virus (Morzunov et al 1998;Song et al 1996;Rhodes et al 2000). In 2012, ten cases of SNV-caused hantavirus infections (HPS) of which three were fatal occurred in Yosemite National Park, California, USA (Center-for- Disease-Control-and-Prevention 2012;Roehr 2012).…”
Section: Hantaviruses In the New Worldmentioning
confidence: 96%